Correlates of duration between initial drug use and first drug injection among people who inject drugs in Iran, 2020 - Zahra Abdolahinia; Zahra Jaafari; Ali Karamoozian; Soheil Mehmandoost; Nima Ghalekhani; Mehrdad Khezri; Ghazal Mousavian; Mostafa Shokoohi; Ali Mirzazadeh; Ali Akbar Haghdoost; Mohammad Karamouzian; Mohammad Mehdi Gooya; et al. (BMC Public Health)
Abstract Background People who use non-injection drug use are at risk of transitioning to injecting drugs, which increases their vulnerability to HIV and other blood-borne infections. This study aimed to investigate the correlates of the duration between the first drug use and the first drug injection among people who inject drugs (PWID) in Iran, as well as the reasons for injection initiation. Methods We analyzed data from the fourth national bio-behavioral surveillance survey among PWID in Iran, conducted in 2020 across 11 cities using respondent-driven sampling (n = 2,684). A generalized linear mixed model with a gamma-distributed dependent variable and log link function was used to investigate the correlates of transition time from non-injection to injection drug use. Results Among 2,356 participants included in the analysis, the mean ± SD of the duration between the first drug use and the first drug injection was 9.37 ± 6.8 years. Factors associated with earlier injection initiation included: age under 30 years (p-value < 0.001), being single (p-value < 0.001) or divorced/widowed (p-value = 0.007), history of incarceration (p-value = 0.001), sexual debut before age 18 (p-value < 0.001), and history of depression (p-value < 0.001). Peer influence (665;29.1%) and pleasure-seeking behavior (534; 23.3%) were the most common motives for injection initiation. Conclusions The transition to injection drug use among PWID in Iran often occurs within a decade of initial drug use and is influenced by demographic, social, and psychological factors. Prevention strategies should focus on early intervention for at-risk youth, address mental health needs, and leverage peer influence. Policymakers should prioritize evidence-based, multi-faceted approaches that target both individual and structural factors to delay or prevent the transition to injection drug use and reduce associated health risks.